Exploring the Economic Prospects and Challenges of Sustainable Waterfront Development in Dhaka City, Bangladesh (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study explores the economic prospects and challenges of sustainable waterfront development in Dhaka City, with a particular focus on the economic aspects.Methods: A qualitative approach was followed, comprising a literature review, field observations, and semi-structured interviews. Data were thematically analyzed across social, environmental, and economic dimensions, with emphasis placed on identifying existing economic activities and assessing their potential for structured business growth.Results: Findings reveal that the Turag riverfront hosts a variety of informal activities and businesses, such as water transportation, street vending, fishing, freight handling, and recreation. Stakeholders’ insights confirmed that although these activities sustain local needs, the absence of organized facilities, weak governance, and environmental degradation constrain its potential as a structured economic hub. International case comparisons from Kyrenia in Cyprus, Jeddah in Saudi Arabia, and Alexandria in Egypt show how the formalization of informal businesses, investment in infrastructure through Public–Private Partnerships, and heritage-based tourism can transform waterfronts into competitive urban economies.Conclusion: The study concludes that economic vitality is central to sustainable waterfront development. Integrating informal activities into formal planning, aligning with national policies such as the Bangladesh Delta Plan 2100, and promoting tourism-oriented investments and Small- and Medium-sized Enterprise–based strategies can enable the Turag riverfront to evolve as an inclusive, sustainable urban development model.